Association Between Body Composition and Performance in the 30-15 Intermittent Fitness Test in Adult Female Professional Soccer Players in Chile; [Asociación Entre la Composición Corporal y el Rendimiento en 30-15 Intermittent Fitness Test en Futbolistas Profesionales Adultas de Chile] - Aedo-Munoz, E (Fundacion Universitaria Maria Cano, 2024)
Background. The participation of women in football has increased exponentially in recent years, so integrating evidence-based background in this population allows a better understanding and analysis of the sporting performance of female athletes. Objective. Determine the level of association between body composition indicators and performance in the 30-15 IFT test in first division female football players. Methods. 29 professional female players from a first division team in Chile partici-pated. The 30-15 test was evaluated, the final velocity achieved (VIFT) was analyzed, and the maximum oxygen consumption (VO2 máx) was estimated. Body composition (CC) was estimated through anthropometry and height, body mass, body mass index (BMI), absolute (AM) and relative (RM) adipose mass, absolute (MM) and relative (RMM) muscle mass, and 6-fold sum (S6P) were analyzed. Pearson’s correlation coef-ficient (r) with an alpha of 0.05 was used to analyze the level of association. Results. Weak negative correlations were found between MA with VIFT (r =-0.384 and p = 0.04) and VO2 máx (r =-0.375 and p = 0.45); moderate negative correlations between S6P with VIFT (r =-0.476 and p = 0.009) and VO2 máx (r = 0.454 and p = 0.013); moderate negative correlations between BMI with VIFT (r = 0.401 and p = 0.031) and VO2 máx (r =-0.379 and p = 0.043). No correlations were found between MM and PMM with VIFT or VO2 máx. Conclusion. It is possible to conclude that performance in the 30-15IFT is associated with body composition, specifically with MA, S6P, and BMI in players evaluated. © 2024. Fundación Universitaria María Cano.